2013
DOI: 10.1177/1352458513508835
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of oral versus intravenous methylprednisolone for relapse of MS

Abstract: clinicaltrials.gov identifier: NCT00753792.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 34 publications
5
76
0
4
Order By: Relevance
“…Oral prednisone, starting at 1 mg/kg/day and tapered over 1-4 weeks, is considered for patients with incomplete resolution of symptoms after IV treatment. There is evidence that high-dose oral corticosteroids (1250 mg of prednisone for adults) may be as beneficial as the IV form for treating acute inflammatory, demyelinating attacks of the CNS [46][47][48]. In children, oral steroids are less commonly used for treating an acute attack as appropriate dosing is unclear.…”
Section: Acute Management Of Demyelinating Attacksmentioning
confidence: 99%
“…Oral prednisone, starting at 1 mg/kg/day and tapered over 1-4 weeks, is considered for patients with incomplete resolution of symptoms after IV treatment. There is evidence that high-dose oral corticosteroids (1250 mg of prednisone for adults) may be as beneficial as the IV form for treating acute inflammatory, demyelinating attacks of the CNS [46][47][48]. In children, oral steroids are less commonly used for treating an acute attack as appropriate dosing is unclear.…”
Section: Acute Management Of Demyelinating Attacksmentioning
confidence: 99%
“…No difference was found between groups regarding drug efficiency with administration of equal doses of oral and IV MP. In a well-designed study in which oral (1250 mg/per day for 3 days) and IV (1000 mg/ per day for 3 days), MP therapies were compared in 49 patients; no differences were found between the groups in the 1 st , 4 th , and 12 th weeks in terms of both reducing EDSS scores and MRI lesions (71). In some centers, oral steroid administration is increased in patients, particularly in those who do not require close monitoring.…”
Section: Adrenocorticotropic Hormone and Steroidsmentioning
confidence: 99%
“…However, a recently published study evaluated oral steroid administration in relapse: Relapses were identified as "severe"(increase >2.5 points on EDSS), "moderate" (increase 1-2.5 points on EDSS), and "mild" (increase ≤0.5 points on EDSS) (38).…”
mentioning
confidence: 99%
“…The trial provided confirmatory evidence that bioequivalent high-dose oMP is not clinically nor radiologically inferior to ivMP, and is equally well-tolerated and safe. 2 All participants in the present study were adults who had met the 2005 McDonald criteria 3 for RRMS, and had experienced a recent (< 15 days) moderate or severe relapse. All patients had an EDSS score ⩽ 5.0, acquired in the previous 6-month relapse-free period (EDSS T-1).…”
Section: Patientsmentioning
confidence: 99%